Design and Test of Auxiliary Harvesting Device of Apple - Wu, Chao; Wang, Yang; Sun, Qun; Zhao, Ying; Zhang, Laigang (Recent Patents on Engineering, 2021)
Background: In the production process of apple orchard, the labor needed for apple harvest accounts about 40% of the whole production process. Objective: The auxiliary device of apple harvest was designed to improve production efficiency and reduce labor cost. Methods: This device was composed of four parts: fruit collecting mechanism, horizontal conveying mechanism, vertical conveying mechanism and rotary packing mechanism, which assists farmers in finishing the process from picking to packaging apples. Simulation and fruit damage analyses were carried out by Solid works, fruit damage included three types: Single collision, Overlapping collision and Multi-zone collision. Results: In the experiment, PID algorithm was employed to control device operate accurately. And when the motor speed were 52 r/min, 56 r/min, 60 r/min, the collection efficiency were 4900 apples/ h, 5300 apples/h, 5700 apples/h and the fruit damage rates were 4%, 5%, 8%. Conclusion: The experimental results indicated that compared with the manual operation and visual recognition-based picking robots this device’s production efficiency was improving without increasing the fruit damage rate.
Keywords: transmission mechanism